Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cells10092371
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1-Independent Mechanisms Regulating Metabolic Adaptation in Hypoxic Cancer Cells

Abstract: In solid tumours, cancer cells exist within hypoxic microenvironments, and their metabolic adaptation to this hypoxia is driven by HIF-1 transcription factor, which is overexpressed in a broad range of human cancers. HIF inhibitors are under pre-clinical investigation and clinical trials, but there is evidence that hypoxic cancer cells can adapt metabolically to HIF-1 inhibition, which would provide a potential route for drug resistance. Here, we review accumulating evidence of such adaptions in carbohydrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 213 publications
0
32
0
Order By: Relevance
“…It is reasonable to assume that between normoxic and necrotic areas, hypoxic cell clones exist. These cells, for example, through—but not only—the hypoxia-inducible factor 1α (HIF-1α) signaling pathway, develop a metabolic adaptation to hypoxia and survive ( 43 ). They may be not actively proliferating but still viable and able to escape from the radiation effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that between normoxic and necrotic areas, hypoxic cell clones exist. These cells, for example, through—but not only—the hypoxia-inducible factor 1α (HIF-1α) signaling pathway, develop a metabolic adaptation to hypoxia and survive ( 43 ). They may be not actively proliferating but still viable and able to escape from the radiation effects.…”
Section: Discussionmentioning
confidence: 99%
“…ARNT, also known as HIF-1β, forming a complex with HIF-1α participates in the emergency response under hypoxic conditions ( Smythies et al, 2019 ). In general, ARNT expression is located in the nucleus, and it forms dimers with HIF-1α under hypoxic conditions, to regulate physiological processes such as angiogenesis and energy metabolism as transcription factor ( Lee et al, 2021 ). Hoang et al showed that ARNT was expressed in islet beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…Translocation resulting from the break apart of 12p13 usually involves ETV6 gene in hematologic malignancies, such as t (5;12) (q31‐33; p13) in chronic myelomonocytic leukemia (Apperley et al, 2002; Di Giacomo et al, 2021) and t (12;21) (p13;q22) in ALL (Montaño et al, 2020; Shurtleff et al, 1995). The aryl hydrocarbon receptor nuclear translocator ( ARNT ) gene, also named HIF‐1β , locates in 1q21, which play a critical role in driving tumor growth and metastasis (Lee et al, 2021). It has been reported as a partner gene of fusion gene in two cases with t(1,12)(q21;p13)(Otsubo et al, 2010; Salomon‐Nguyen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%